2005
DOI: 10.1097/01.ccm.0000149854.61192.dc
|View full text |Cite
|
Sign up to set email alerts
|

Lower tidal volume ventilation and plasma cytokine markers of inflammation in patients with acute lung injury*

Abstract: In patients with acute lung injury, plasma interleukin-6 and interleukin-8 levels are associated with morbidity and mortality. The severity of inflammation varies with clinical risk factor, suggesting that clinical risk factor should be considered when both developing and testing therapeutic interventions. Low tidal volume ventilation is associated with a more rapid attenuation of the inflammatory response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

32
444
4
19

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 642 publications
(499 citation statements)
references
References 36 publications
32
444
4
19
Order By: Relevance
“…Parsons and colleagues support the interpretation that inflammation and mechanical injury are pathophysio logically linked in the lungs, because a simple intervention, reducing tidal volume, reduced systemic inflammation and also improved outcome (35). Thus, a portion of the lung inflam matory response is likely to be a consequence of direct mechanical injury to the lung parenchyma and circulating cytokines are markers of this inflammatory response.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Parsons and colleagues support the interpretation that inflammation and mechanical injury are pathophysio logically linked in the lungs, because a simple intervention, reducing tidal volume, reduced systemic inflammation and also improved outcome (35). Thus, a portion of the lung inflam matory response is likely to be a consequence of direct mechanical injury to the lung parenchyma and circulating cytokines are markers of this inflammatory response.…”
Section: Discussionmentioning
confidence: 96%
“…There is strong evidence that IL6, IL8 and IL10 are useful circulating markers of the intensity of the inflam matory response in the lungs and the prognosis of patients at the onset of lung injury (35). Parsons and colleagues support the interpretation that inflammation and mechanical injury are pathophysio logically linked in the lungs, because a simple intervention, reducing tidal volume, reduced systemic inflammation and also improved outcome (35).…”
Section: Discussionmentioning
confidence: 99%
“…Additional studies from this trial demonstrated that, in patients with ALI, baseline plasma levels of IL-6, -8 and -10 were associated with increased mortality and a decrease in ventilator-free and organ failurefree days. Patients receiving lower tidal volumes had reduced plasma levels of IL-6 and -8, indicating that ventilatory management can modify circulating inflammatory cytokines [54].…”
Section: Epithelial Cell Responses To Mechanical Stretchmentioning
confidence: 99%
“…Additional studies from this trial demonstrated that, in patients with ALI, baseline plasma levels of IL-6, -8 and -10 were associated with increased mortality and a decrease in ventilator-free and organ failurefree days. Patients receiving lower tidal volumes had reduced plasma levels of IL-6 and -8, indicating that ventilatory management can modify circulating inflammatory cytokines [54].Another study of a lung-protective strategy demonstrated reduced lung inflammation and reduced concentrations of inflammatory cytokines in plasma and bronchoalveolar lavage (BAL) fluid associated with a lung-protective strategy [55]. Stuber and colleagues examined the kinetics of cytokine expression associated with tidal volume changes.…”
mentioning
confidence: 99%
“…1995; Parsons et al. 2005). It has also been shown that IL‐6 may be a useful biomarker for stratification of asthma patients by reflecting poor lung function and increased risk for developing exacerbations (Peters et al., 2016).…”
Section: Discussionmentioning
confidence: 99%